KONSTITUSIONALITAS PERUBAHAN USIA CALON PRESIDEN DAN CALON WAKIL PRESIDEN DALAM NEGARA HUKUM DEMOKRASI. - Adji, Agung Bayu; Mau, Hedwig Adianto; Candra, Mardi (LPPM Institut Pendidikan Nusantara Global, 2024)
As a state of law, Indonesia's system of government is based on the principle of the constitution. As a consequence, democracy has become a system that is implemented through the holding of general elections for president and vice president. The change in the age limit of presidential and vice-presidential candidates in Article 169 letter q of Law Number 7/2017 has undergone changes in accordance with the Constitutional Court Decision Number 90/PUU-XX 11/2023 which has caused controversy from various parties, namely the Constitutional Court Decision Number 90/PUU-XX 11/2023 has the potential to violate the principles in the exercise of judicial power, has a major impact on the good name of the Constitutional Court and Indonesian law, and there are a number of irregularities in several decisions of the Constitutional Court that test the constitutionality of Article 169 letter q. This research uses a normative juridical method. The research method in this study is the normative juridical method. The type of data used by the author is secondary data with primary legal materials, secondary legal materials, and tertiary legal materials. Data collection techniques in the form of documents or library materials on secondary legal data. The data analysis method in this research is descriptive qualitative. The results showed that the age limit for presidential and vice presidential candidates is regulated in Article 169 letter q of Law Number 7/2017 on General Elections. The series of legal rules for the election of the president and vice president in accordance with the mandate of the 1945 Constitution of the Republic of Indonesia Article 22E are set out in several amendments to the rules, namely Law Number 23 of 2003, the second amendment is contained in Law Number 42 of 2008 concerning General Elections of the President and Vice President and finally amended into Law Number 7 of 2017 concerning General Elections. The implications of changes in the age of presidential and vice-presidential candidates in a democratic legal state as outlined in Constitutional Court Decision Number 90/PUU-XXI/2023 are essentially adding norms that should not be in accordance with the initial principles of the Constitutional Court (testing the constitutionality of existing norms), the Constitutional Court's decision cannot be separated from the political context, the Constitutional Court's decision was not taken unanimously because there were differences of opinion among the panel of judges, and there were several striking anomalies, especially in the considerations presented in the dissenting opinion and concurring opinion